“Wriggling parasite inside the bladder” : case report in Semarang, Indonesia - Yohanes Dona Christi Utama; Dimas S. Wibisono; Yustina Elisa Febriany (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2021)
Introduction & Objectives: Finding